MEDIUM-TERM EXPENDITURE FRAMEWORK (MTEF) AND REALISTIC BUDGETING IN KADUNA STATE - BOGNET, CYPRAIN ALFRED; MENSON, AUTA ELISHA; BODAM, SERAH NDAK; MAISAMARI, FAVOUR KAJYUNG; SAMUEL, FIDELIS; YUSUF, MOHAMMED; SANI, MAHMUD NUHU; YAKUBU, MENDOS TITUS; ZINOM, YASHIM JOSHUA (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
Despite the implementation of the MTEF to guide realistic budgeting, significant gaps persist, leading to questions about the framework’s effectiveness in achieving accurate and efficient public financial management. This study is focused on analyzing revenue and expenditure projections in Kaduna State from 2016 to 2023; determining whether the MTEF leads to realistic budgets or not and identifying the key challenges affecting the effectiveness of MTEF. The study employs a mixed-method approach, combining quantitative analysis of financial data from 2016 to 2023 with a survey of 50 MTEF and budget stakeholders. The quantitative analysis examines discrepancies between budget estimates, MTEF projections, and actual expenditures, while the survey gathers stakeholder perspectives on the effectiveness and challenges of MTEF implementation. The analysis reveals consistent overestimation of budgetfigures compared to MTEF projections and actual expenditures, highlighting issues in maintaining fiscal discipline and realistic budgeting. Based on the findings, this study therefore concludes that MTEF has not led to realistic budgeting due to political interference, data reliability concerns, capacity constraints, and poor stakeholder engagement. The study thus recommends Improve Data Quality, Strengthen Fiscal Discipline, Increase Stakeholder Engagement, reduction of political Interference, and capacity building. By implementing these recommendations, Kaduna State can improve its budgeting process, leading to more efficient public financial management and better alignment of budget estimates with actual economic conditions